Schools and the prevention of petty crime: Search for a missing link - Baerveldt, Chris (Journal of quantitative criminology, 1992)
Earlier research on the relation between school features and petty crime suggests that schools can intentionally influence the crime rate of the pupils. These findings were the starting point for a Dutch study at secondary schools of the same type in Dutch towns. The study focused on effects on the delinquency of third-year low-stream pupils (aged 15–17). For the study a control theory was formulated, a conditional control theory, which, in contrast to Hirschi's social control theory, recognizes possible delinquent influences of the pupils' network. In the study a strong statistical relation between integration of pupils in school and petty crime was found. However, I found almost no influence of the studied school features on integration and petty crime. These results led to the question whether “the real important feature” of schools had been neglected in the study. This seems not to be the case. A multilevel analysis shows that it is unlikely that there is major impact of schools on the integration of pupils, on delinquency, or on the relationship between integration and delinquency. This can be the result of special aspects of the Dutch school system and of the neglect of theory in earlier research.